2022
DOI: 10.1002/admi.202200042
|View full text |Cite
|
Sign up to set email alerts
|

Configuration of Methylammonium Lead Iodide Perovskite Solar Cell and its Effect on the Device's Performance: A Review

Abstract: Since it is a source of clean energy, harnessing solar power is a natural solution to resolving the prevalent energy crisis. A solar cell is the most effective device to convert solar energy into electricity. Hence, a study on solar cells is the utmost area of interest in the energy sector.As illustrated in Figure 1, there are three generations of solar cells. Among these, the first-generation cells were of p-n homojunction on a silicon crystal, where the thickness of the absorbing layer was more than 180 µm. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 379 publications
(596 reference statements)
0
8
0
Order By: Relevance
“…The performance of perovskite solar cells is influenced by several factors, such as the fabrication atmosphere, device configuration, and charge transporting layers. [ 40–45 ] Therefore, a direct comparison between our results and those reported in the literature may not be suitable. However, it is evident that the performance of the cell in our study can compete with those reported in the literature, indicating that the gas‐quenching approach applied in our study can serve as a viable alternative to the other approaches used in the literature.…”
Section: Resultsmentioning
confidence: 80%
“…The performance of perovskite solar cells is influenced by several factors, such as the fabrication atmosphere, device configuration, and charge transporting layers. [ 40–45 ] Therefore, a direct comparison between our results and those reported in the literature may not be suitable. However, it is evident that the performance of the cell in our study can compete with those reported in the literature, indicating that the gas‐quenching approach applied in our study can serve as a viable alternative to the other approaches used in the literature.…”
Section: Resultsmentioning
confidence: 80%
“…Thereby, the following configurations were considered for the valence electrons: Cs (5s 2 , 5p 6 , 6s 1 ), H (1s 1 ), C (2s 2 , 2p 2 ), N (2s 2 , 2p 3 ), Pb (5s 2 , 5d 10 , 6s 2 , 6p 2 ), and I (5s 2 , 5p 5 ). The integration over the Brillouin zone were calculated via DFT-1/2 quasiparticle correction, 56 which is based on Slater's half-ion technique.…”
Section: Total Energy Calculations and Geometry Optimizationmentioning
confidence: 99%
“…Metal halide perovskites (MHPs) applied in photovoltaic devices, such as perovskite solar cells (PSCs), have achieved power conversion efficiencies (PCE) as high as 22.54% for MAPbI3 1 . This impressive performance can be attributed to their suitable optical and electronic properties, such as high absorption coefficients in the UV–visible region, 2–4 low exciton binding energies, 5–8 and long carrier lifetimes 9 and diffusion lengths 10 .…”
Section: Introductionmentioning
confidence: 99%
“…Halide perovskites have acted well in outstanding solar cells which achieved a best efficiency of 25.7% [ 1 5 ] and are driving current photovoltaic technology development [ 6 8 ]. Nevertheless, the weak stability of halide perovskites stays an essential problem that has to be addressed before this low-priced and solution-processable photovoltaic equipment can be commercialized on a large scale [ 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%